ZIKA VIRUS: A REVIEW FROM THE VIRUS BASICS TO PROPOSED MANAGEMENT STRATEGIES - Lorenzo Zammarchi; Michele Spinicci; Michele Spinicci; Alessandro Bartoloni; Alessandro Bartoloni (Mediterranean Journal of Hematology and Infectious Diseases)
This review aims to summarize the body of knowledge available on Zika virus to date. A comprehensive review of the scientific literature on Zika virus was performed with the aim to stress relevant aspects for healthcare professionals in non-endemic area. For several years, the Zika virus infection was considered an extremely rare exotic disease with poor clinical relevance. However, Zika virus has recently gained the attention of the scientific community and public opinion since the virus spread to the Pacific islands and the South America in an unprecedented epidemic, and additionally due to the definitive evidence that the infection could be complicated by Guillain-Barré syndrome, passed through vertical transmission, and result in central nervous system abnormalities (including microcephaly) of the fetus. Studies and scientific evidences on the complications associated with Zika virus infection are growing day by day. It is advisable that the healthcare professionals working in non-endemic areas maintain full awareness on this issue in order to practice proper management of the imported cases of Zika virus infection.